Handbook of career development : international perspectives - Bakshi, Anuradha J.; Leong, Frederick T. L.; Watts, A. G.; Arulmani, Gideon (International and Cultural Psychology, 2014)
As a quintessentially human activity, work transcends countries and cultures.  But as economies falter and labor markets go global, the concept of career can seem unrealistic-even alien-to many in economically developing and developed nations alike.  The challenge to today's career professional is providing relevant services in the face of rapid, pervasive change. The Handbook of Career Development assembles theoretical and practical innovations on a world scale.  Written by professionals from diverse countries and fields, this progressive resource presents career guidance and workforce development as cross-cultural, multidisciplinary, and responsive to contemporary realities.  Advanced analysis allows a deeper understanding of the long-term needs of workers as varied as indigenous peoples, older women, immigrants, international students, and the recovering mentally ill.  Easy-to-apply career service strategies are outlined for each of these special groups as also for others.  And the book's multicultural vision entails reinterpreting the notion of career for the economically developing world, including for those engaged in traditional, rural and craft occupations.  Among the areas covered in the Handbook:  Innovations in career theory. The person in contexts across the lifespan. Effective career preparation in a volatile labor market. Green careers: work, environmental sustainability, and social justice. Enabling culturally sensitive career counseling. Services for special groups. New directions for assessment, practice, counselor training, competencies, and standards. The Handbook of Career Development opens out realistic new paths for all involved in career services, including counselors, psychologists, social workers, human resource managers, educators, youth workers, and policymakers.  It is a suitable resource for a range of academic fields such as developmental studies, economics, ecology, and indigenous studies, and makes an invaluable training text for aspiring career counselors.